The Effect of the Use of Digital Book Media on the Reading Ability of Class I of SDN 23 Cakranegara - Wahyudi, Dikky; Dewi, Nurul Kemala; Rahmatih, Aisa Nikmah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to determine the effect of using digital book media on the reading skills of grade 1 students of SDN 23 Cakranegara. This research uses experimental research with the type of quantitative research type One Group Pretest-Posttest. The results of data analysis using the paired sample t-test test obtained a sig value (2-tailed) of 0.009 < 0.05, if the significance value (P < 0.05) then the data has a significant difference. So it can be concluded that there is a significant difference using digital book media. The results of the hypothesis test show that Ho is rejected and Ha is accepted, meaning that there is an effect of using digital book media on the reading ability of grade 1 students of SDN 23 Cakranegara in the 2023/2024 academic year.